Ground Deformation Characteristics Induced by Mechanized Shield Twin Tunnelling along Curved Alignments. (8th February 2021) - Wu, Dangzhong; Xu, Kaiping; Guo, Panpan; Lei, Gang; Cheng, Kang; Gong, Xiaonan
Abstract : This paper investigates the ground deformation characteristics induced by mechanized shield twin tunnelling along curved alignments by adopting the nonlinear three-dimensional (3D) finite element method (FEM). The performance of the adopted FEM is demonstrated to be satisfactory by comparing the numerical analysis results with the field monitoring data in a typical case history and with the predicted results generated by a modified version of the Peck's empirical Gaussian formula. It has been found that the tunnelling-induced transverse ground surface settlement troughs and the distributions of the subsurface horizontal and vertical ground displacements are mostly similar in both form and magnitude for the considered various radii of curvature of tunnel alignment including 50 m, 100 m, 150 m, 200 m, 250 m, 300 m, 400 m, and infinity (i.e., straight-line tunnel). Considering the variational characteristics of the ground deformations with the magnitude of the radius of curvature, the radius of curvature of 100 m can be regarded as a critical tunnel alignment radius of curvature controlling the transformation of the curved tunnelling-induced ground deformational behaviors. For the benefit of geotechnical engineers interested in curved tunnelling with a small radius of curvature, a discussion of the technologies for reducing the overexcavation and improving the accuracy of tunnel lining segment installation is also presented.